The Failure Factors of Collective Action in Promoting the Recognition of Customary Forest: Case of Kenegerian Rumbio Customary Forest in Riau Province - Fahrul Rozi Sembiring; Leti Sundawati; Bramasto Nugroho (Jurnal Manajemen Hutan Tropika, 2021)
One of the five schemes in social forestry program in Indonesia is customary forest recognition. Kenegerian Rumbio Customary Forest, a customary forest in Riau Province, is failed in the recognition process. The objectives of this study are to analyze the failure factors of collective action and to formulate strategies to encourage the success of collective action on recognition of Kenegerian Rumbio Customary Forest. This research was built by using both quantitative and qualitative approach where the data were collected by using survey and in-depth interviews. The research results found that improper facilitation caused by communication issues between involved parties, the absence of the symbolic power, the failure in forming the common knowledge are the factors leading to the failure of collective action. To reconstruct the collective action, this study offered four strategies: (1) to frequently communicate with personal approach to the two highest indigenous leaders with whom facilitators have difficulty communicating well, (2) to mediate the two conflicted indigenous leaders for generating their motivation to propose their forest, (3) to conduct socialization to all indigenous leaders (40 jini) and community representatives to increase an understanding regarding the purpose and importance of recognition of customary forest, and (4) to conduct a participatory mapping to reduce area border issues among two sub-tribes.